Analysis of exhaled human breaths using graphene gas sensor based on the male gender - Shamsudin, Nur Hazahsha; Jalan, Calvin Jeffry; Mohd Chachuli, Siti Amaniah; Coban, Omer; Waeleh, Nazreen; Md Junos@Yunus, Siti Aisah; Selamat, Nur Asmiza; Mohd Ali, Nursabillilah (Semarak Ilmu Publishing, 2025)
Breath analysis is an intriguing method that has the potential to significantly improve non-implantable physical health management via the use of flexible sensors to monitor breathing behaviours. In comparison to other analytical techniques for detecting breath elements, non-invasive breathing diagnostics based on chemical sensors can provide numerous benefits, including nanotechnology, power efficiency, simplicity of structure, and cost-effectiveness, contributing to the flexibility of experimental studies. This paper presents the graphene-based human breath sensor. Graphene was prepared in a paste form by mixing the graphene powder with two types of the binder. Two binders were prepared to compare their performance to human breath. The graphene paste was deposited using screen-printing on different substrates, Kapton film, and glass. The sensing film was thermally annealed at 200°C for 30 minutes and characterized using SEM and FTIR. All graphene gas sensor samples responded well to collected male human breath samples: Bumiputera (Sarawak), Malay, Chinese, and Indian. The best graphene gas sensor for males was OG-T(G) and OG-T(K) with sensitivity, S=1.10415 and S=1.01629. Based on the comparison results of male human breath, the fastest response time and recovery time were 0.52s and 13s, respectively.